Ielts writing assessment criteria - Жукова, Тетяна Василівна; Жукова, Татьяна Васильевна; Zhukova, Tetiana (ТГАТУ, 2017)
The main criteria for international writing assessment are sub-stantiated in the article. The most important features of academic writing in English are lighted.
Keywords: academic writing; band descriptors; cohesion; coherence; lexical resources; task achievement; grammar